Comparison of Spectrophotometric Methods of Total Flavonoid Assay Based on Complex Formation with Aluminum Chloride as Applied to Multicomponent Herbal Drug Angionorm (Journal of Pharmaceutical Negative Results, 2018)
Objective: The objective was to compare the complex formation of flavones (luteolin, apigenin), flavonols (morin, quercetin, and rutin),flavanones (naringenin), flavanonols (dihydroquercetin), caffeic, and ferulic acids with aluminum ion using two spectrophotometric methodsand the application of these methods to estimate the flavonoid content in the angionorm herbal product. Materials and Methods: Method 1included direct complex formation with aluminum chloride, and Method 2 involved preliminary nitrozation and subsequent complex formationof nitroso‑derivatives with aluminum chloride. 2,4‑dinitrophenylhydrazine method was also tested. Results: The conjugation system increasein the chromophore structure of nitroso derivatives is reflected by the hyperchromic effect of all substances (from 1.4 to 4‑fold). The largestbathochromic shift of nitroso derivatives was seen for rutin, luteolin, and dihydroquercetin (to 510–530 nm). The total flavonoids estimationin the extract of the four herbs mixture, which constitute angionorm preparation active ingredient, depends on the chosen reference substance(3.49% calculated as luteolin when measured by Method 1 or 8.71% by Method 2; 7.97% calculated as dihydroquercetin when measured byMethod 1 and 4.14% by Method 2. Conclusion: The complex formation according to Methods 1 and 2 does not allow the identification ofthe selective spectral regions typical for the certain flavonoids subgroups and hydroxycinnamic acids. Neither method of complex formationis suitable for the assay of total flavonoids in unknown samples or for the flavonoid content comparison in the different herbal material.